A cross-cultural comparison of organizational communication media: an application of media richness theory - Abdel Kader, Mai Wahid (AUC Knowledge Fountain, 2010)
Media Richness Theory (MRT) argues that within any work organization, the performance of employees and managers improve when using â richer' media for equivocal tasks. The main goal of this study is to assess the predictions made by Media Richness Theory that richer communication is better for tasks which are perceived to be equivocal. The employees' media selection behavior was assessed in accordance with the MRT to test its validity and application. This study sought to evaluate whether or not the assumptions made by MRT hold across the different cultural settings within organizations by distinguishing between high-context collectivistic cultures and low-context individualistic ones. To test this, a cross-cultural study of 312 employees and managers in Egypt, United Arab Emirates, Lebanon, Jordan, Kuwait, Tunisia, Bahrain representing high-context collectivistic cultures, and Canada, USA, UK, Germany, France, Czech Republic, and Switzerland representing low-context individualistic cultures was conducted. Based on the results, the applicability of MRT in organizations and across cultures was discussed.